Lepton masses in a supersymmetric 3-3-1 model - Montero, J. C.; Pleitez, V; Rodriguez, M. C. (American Physical Soc, 2002)
We consider the mass generation for both charginos and neutralinos in a 3-3-1 supersymmetric model. We show that R-parity breaking interactions leave the electron and one of the neutrinos massless at the tree level. However, the same interactions induce masses for these particles at the 1-loop level. Unlike the similar situation in the minimal supersymmetric standard model, the masses of the neutralinos are related to the masses of the charginos.